Optimal control for a prototype of an active magnetic bearing system - Aragón Ayala, Danielo Eduardo (2017)
First applications of the electromagnetic suspension principle have been in experimental physics, and suggestions to use this principle for suspending transportation vehicles for high-speed trains go back to 1937. There are various ways of designing magnetic suspensions for a contact free support, the magnetic bearing is just one of them [BCK+09]. Most bearings are used in applications involving rotation. Nowadays, the use of contact bearings solves problems in the consumer products, industrial machinery, or transportation equipment (cars, trucks, bicycles, etc). Bearings allow the transmition of power from a motor to moving parts of a rotating machine [M+92]. For a variety of rotating machines, it would be advantageous to replace the mechanical bearings for magnetic bearings, which rely on magnetic elds to perform the same functions of levitation, centering, and thrust control of the rotating parts as those performed by a mechanical bearing. An advantage of the magnetic bearings (controlled or not) against purely mechanical is that magnetic bearings are contactless [BHP12]. As a consequence these properties allow novel constructions, high speeds with the possibility of active vibration control, operation with no mechanical wear, less maintenance and therefore lower costs. On the other hand, the complexity of the active (controlled) and passive (not controlled) magnetic bearings requires more knowledge from mechanics, electronics and control [LJKA06]. The passive magnetic bearing (PMB) presents low power loss because of the absence of current, lack of active control ability and low damping sti ness [FM01, SH08]. On the other hand, active magnetic bearing (AMB) has better control ability and high sti ness, whereas it su ers from high power loss due to the biased current [JJYX09]. Scientists of the 1930s began investigating active systems using electromagnets for high-speed ultracentrifuges. However, not controlled magnetic bearings are physically unstable and controlled systems only provide proper sti ness and damping through sophisticated controllers and algorithms. This is precisely why, until the last decade, magnetic bearings did not become a practical alternative to rolling element bearings. Today, magnetic bearing technology has become viable because of advances in microprocessing controllers that allow for con dent and robust active control [CJM04]. Magnetic bearings operate contactlessly and are therefore free of lubricant and wear. They are largely immune to heat, cold and aggressive substances and are operational in vacuum. Because of their low energy losses they are suited for applications with high rotation speeds. The forces act through an air gap, which allows magnetic suspension through hermetic encapsulations [Bet00].